Analysis of the Relationship Between Image, Social Media, and Attitude to Predict Intention to Choose: An Empirical Investigation of Presidential Election in Indonesia - Sihombing, Sabrina O. (International Review of Management and Marketing, 2019)
Research focusing on presidential, regional, and legislative elections has been conducted by previous researchers. However, there is little research comparing business and non-business respondents in predicting presidential intentions. Therefore, this study aims to compare student respondents from business schools and non-business students in predicting the intention of choosing a president. Moreover, Indonesia will undergo presidential election in 2019 where young voters such as college students are voters in significant amounts. Young voters are often identified as swing voters which their attitudes toward the candidates they choose are influenced by information from social media and the image of the presidential candidate. This study involved 214 respondents from both science and non-science education background. The data was analyzed by applying the structural equation modeling. The results of the study showed that there was no difference in study results for respondents with scientific backgrounds and respondents with non-scientific backgrounds. Both types of respondents show the same results that only 1 dimension of the variable of image that has a positive relationship with the attitude towards the candidate candidates. This dimension is charm. The result also shows that there is significant relationship between attitudes toward choosing the candidate with intention to choose the candidate. This study provides results discussion, managerial implications, and recommendation for future research. Keywords: intention, attitude, image, social media JEL Classifications: M30, M31, L82 DOI: https://doi.org/10.32479/irmm.8386